PERENCANAAN PAJAK, PERLUKAH? KAJIAN PRAKTIS MENUJU ADMINISTRASI PERPAJAKAN YANG EFISIEN - Abdul Rahman (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Tax is one of the most potential national income sources for funding the development programs of the country. From economic viewpoint, tax represents the resource transfer from private sector to public sector which is more or less influencing the purchasing power or expense energy of the private sector. For corporate world, tax means expenditure without getting an immediate direct return. In executing taxation, government sees it differently from taxpayers. The government tries to collect as much tax as possible from taxpayers while the tax payers do the opposite. In order to promote better tax obligation to taxpayers,government should strive for improved tax management through tax planning. Tax planning attempts at formulating a suitable type of tax regulation to be implemented by which the burden of taxpayers can be adjusted up to its most proportionate level.